STABILIZATION OF LUBRICATING MATERIALS OPERATIONAL PROPERTIES BY THE TREATMENT WITH ELECTROSTATIC FIELD - Boychenko, Sergey V.; Trofimov, Igor L.; Radomska Мargaryta М. (Proceedings of National Aviation University, 2009)
The influence of imposed external electromagnetic and electrostatic fields is investigated based on operational properties of lubricating environments. The device for the improvement of lubricating materials operational properties is developed and principles of its work are described. Based on the experimental results and analysis of publications the increase of lubricating materials and tribotechnical systems resource enhancement by the means of electrostatic field is grounded.